2019
DOI: 10.2196/15489
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Intervention Effects on Depressive Symptoms Among People Living With HIV: Secondary Analysis of a Mobile Health Randomized Controlled Trial Using Latent Growth Curve Modeling

Abstract: BackgroundAlthough several studies have investigated the effects of mobile health (mHealth) interventions on depression among people living with HIV, few studies have explored mediators of mHealth-based interventions to improve mental health in people living with HIV. Identifying influential mediators may enhance and refine effective components of mHealth interventions to improve mental health of people living with HIV.ObjectiveThis study aimed to examine mediating factors of the effects of a mHealth intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…However, literature examining the mechanisms of QOL improvement in psychosocial interventions are scarce, especially in the long term. In addition, methods employed in previous studies such as repeated measures analyses of covariance and latent growth curve model could not identify the sequential and causal relationships when exploring intervention mechanisms [ 16 , 17 , 56 ]. Our study contributed to the literature by affirming the sequential and potential causal relationships between HIV-related stigma, depressive symptoms, and QOL, which have not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature examining the mechanisms of QOL improvement in psychosocial interventions are scarce, especially in the long term. In addition, methods employed in previous studies such as repeated measures analyses of covariance and latent growth curve model could not identify the sequential and causal relationships when exploring intervention mechanisms [ 16 , 17 , 56 ]. Our study contributed to the literature by affirming the sequential and potential causal relationships between HIV-related stigma, depressive symptoms, and QOL, which have not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study contributed to the literature by affirming the sequential and potential causal relationships between HIV-related stigma, depressive symptoms, and QOL, which have not been reported in previous studies. Furthermore, only a small number of studies used longitudinal data, of which, to the best of our knowledge, none examined the sequential relationships [ 16 , 17 , 56 ]. In this study, the use of SEM with longitudinal data allowed us to assign mediators and the outcomes in chronological order, thus shedding light on the potential causal relationships of the intervention mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…SEM model fit was assessed with Chi-squared (χ 2 ), comparative fit index (CFI), root mean square error of approximation (RMSEA) and standardized root mean square residual (SRMR), with good model fit indicated by non-significant χ 2 , χ 2 /df < 2-5, CFI > 0.90-0.95, RMSEA < 0.06-0.10 and SRMR < 0.05-0.08. 34,35 Multicollinearity was assessed with variance inflation factors (VIFs) and condition indices, with lack of problematic multicollinearity indicated by VIFs < 5-10 and condition indices < 10-30. 36,37…”
Section: Methodsmentioning
confidence: 99%
“…Third, as all the 6 dimensions of QOL were improved in the intervention group at 3, 6, and 9 months, and the improvement was not limited to the mental health dimension, it is possible that the improvement in QOL was also related to other factors besides positive coping, such as reduced depressive symptoms, stress, and/or HIV-related stigma and increased social support [51][52][53]. Although it is beyond the scope of this study to incorporate other factors, one of our previous studies found mediating roles of perceived stress and depressive symptoms for suicide reduction [53], whereas another study found positive coping and HIV-related stigma as intervention mediators on depressive symptoms [52]. Therefore, other potential mediators should be further explored to clarify the mechanisms of intervention effects and processes of how mHealth interventions improve health outcomes for better designing and implementing effective mHealth interventions.…”
Section: Limitationsmentioning
confidence: 99%